Annual Plan Progress Report 1967-68 Government of Madhya Pradesh - Planning Commission (Planning Commission, 1967)
The economy of Madhya Pradesh is predominantly agricultural and about 80 per cent of its population depends on it. The State has a population of 32.37 millions as per 1961 census which amounts to about 7.38 per cent of the population of the Indian Union. With its central location and abundant mineral, forest and hydel resources, it has great potential for development. A solid base has been laid for exploiting these potentialities by substantially stepping up power generating capacity and creating other infrastructure. But despite all these favourable circumstances, the state continues to be one of the most backward regions of the country chiefly due to inadequacy of investment both in the public and private sectors.
Directorate of Economics and Statistics Madhya Pradesh